Accounting and Finance for Non-Specialists / Third Edition - Atrill Peter; Mclaney Eddie (Prentice Hall, 2001)
This text introduces the basic principles and underlying concepts of accounting and finance. Preface, Acknowledgements, Introduction to Accounting and Finance, Measuring and Reporting Financial Position, Measuring and Reporting Financial Performance, Accounting for Limited Companies, Measuring and Reporting Cash Flows, Analysis and Interpretation of Financial Statements, Cost-Volume-Profit Analysis, Full Costing, Budgeting, Capital Investment Decisions, The Management of Working Capital, Financing the Business, Index.